2011
DOI: 10.1051/0004-6361/201117441
|View full text |Cite
|
Sign up to set email alerts
|

Vortices in simulations of solar surface convection

Abstract: We report on the occurrence of small-scale vortices in simulations of the convective solar surface. Using an eigenanalysis of the velocity gradient tensor, we find the subset of high-vorticity regions in which the plasma is swirling. The swirling regions form an unsteady, tangled network of filaments in the turbulent downflow lanes. Near-surface vertical vortices are underdense and cause a local depression of the optical surface. They are potentially observable as bright points in the dark intergranular lanes.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
95
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 26 publications
25
95
0
Order By: Relevance
“…Either it diffuses into the magnetic features across field lines, which runs counter to the estimates of Hasan & Schüssler (1985), or the lifetimes of BPs, i.e., kilogauss features are rather short, or the plasma with the strong field is continually mixing with relatively field-free plasma in the immediate surroundings of the magnetic elements. This last process may be related to the vortices found in the simulations around magnetic elements by, e.g., Moll et al (2011), and observationally by Bonet et al (2010) and Wedemeyer-Böhm et al (2012).…”
Section: Discussionmentioning
confidence: 58%
“…Either it diffuses into the magnetic features across field lines, which runs counter to the estimates of Hasan & Schüssler (1985), or the lifetimes of BPs, i.e., kilogauss features are rather short, or the plasma with the strong field is continually mixing with relatively field-free plasma in the immediate surroundings of the magnetic elements. This last process may be related to the vortices found in the simulations around magnetic elements by, e.g., Moll et al (2011), and observationally by Bonet et al (2010) and Wedemeyer-Böhm et al (2012).…”
Section: Discussionmentioning
confidence: 58%
“…The comparison with the magnetic-field distribution in the third row indicates that the horizontal vortices near z = 0 are a hydrodynamical phenomenon of the overturning motions at the borders of granules, which is essentially unrelated to the intergranular magnetic flux concentrations (cf. Steiner et al 2010;Moll et al 2011). In contrast to this, the vertical vortices are almost exclusively found in magnetic flux concentrations.…”
Section: Vortex Identificationmentioning
confidence: 87%
“…For instance, a purely bidirectional shear flow without any rotational component nevertheless has a non-vanishing vorticity. For the detection of vortices, i.e., fluid elements rotating about a local, possibly moving axis, we followed the procedure employed in Moll et al (2011): vortices (swirling flows) are defined as regions where the velocity gradient tensor has a pair of complex conjugate eigenvalues (Zhou et al 1999). The strength of the vortical motion is determined by the swirling strength, λ ci , which is the magnitude of the unsigned imaginary part of the complex eigenvalues.…”
Section: Vortex Identificationmentioning
confidence: 99%
“…Bonet et al 2008Bonet et al , 2010Steiner et al 2010;Vargas Domínguez et al 2011;Wedemeyer-Böhm et al 2012) and also in solar simulations (e.g. Stein & Nordlund 1998;Moll et al 2011). Ludwig et al (2006 reported swirling downflows also in simulations of cool main-sequence stars of spectral type M.…”
Section: Vortex Motionsmentioning
confidence: 95%
“…Analogous to small-scale bright magnetic features (magnetic bright points), for which the depressions of the optical surface are caused by the magnetic pressure, the vortex flows sometimes can appear as features of enhanced intensity due to side-wall heating of the interior of the depression. The vortices in solar MURaM simulations are described in detail by Moll et al (2011Moll et al ( , 2012.…”
Section: Vortex Motionsmentioning
confidence: 99%